We have to prove that `8*cos^2x + cos 4x = 8*cos^4x + 1`

Starting with the left hand side:

`8*cos^2x + cos 4x`

=> `8*cos^2x + (cos^2(2x) - sin^2(2x))`

=> `8*cos^2x + (cos^2x - sin^2x)^2 - (2*sin x*cos x)^2`

=> `8*cos^2x + cos^4x + sin^4x - 2*cos^2x*sin^2x - 4*sin^2x*cos^2x`

=> `8*cos^2x + cos^4x +(1 - cos^2)^2 - 6*cos^2x(1 - cos^2x)`

=> `8*cos^2x + cos^4x +1 +cos^4x - 2*cos^2x - 6*cos^2x + 6*cos^4x`

=> `8*cos^4x + 1`

**This proves the identity:** `8*cos^2x +cos 4x = 8*cos^4x + 1`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now